PROBLEM ISSUES OF CLAIMS OF EVIDENCE IN COMMERCIAL JURISDICTION - Timush, Iryna; Slobodska, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The method of the article is to study the current legislative acts, normative documents and judicial practice, which regulate the process of collection and use of evidence in economic litigation. Therefore, the goal is to reveal the system of legal norms, procedures and principles that determine the legal regulation of the demand for evidence in economic proceedings; study of the practice of demanding evidence in economic litigation and the main shortcomings of this process. The methodological basis of the research was made up of general scientific and special methods: formal-logical, dialectical, system analysis, analytical-synthetic. In particular, the dialectical method was applied in the study of the theoretical aspects of the legal nature of the demand for evidence in the economic process. The methods of analysis and synthesis were used in formulating theoretical conclusions, proposals for improving the current legislation of Ukraine and recommendations for its application. With the help of the formal-logical method, the provisions of the current economic and procedural legislation of Ukraine were investigated and its shortcomings were identified. According to the results of the conducted research, it becomes clear that the legal nature of the demand for evidence is ambiguous, and there is also a significant difference in the grounds for the demand for evidence, the terms for the implementation of procedural law, the court hearing, the possibility of appealing decisions on the demand for evidence or the provision of evidence. Discussion: in the fair, impartial and timely resolution of disputes by the court, the leading place is occupied by the study of evidence. According to Art. 73 of the Commercial Procedure Code of Ukraine (hereinafter - the Code of Civil Procedure of Ukraine), evidence in a commercial proceeding is any data on the basis of which the court establishes the presence or absence of circumstances (facts) that substantiate the claims and objections of the parties to the case, and other circumstances that are significant to solve the case. These data are established by the following means: 1) written, physical and electronic evidence; 2) conclusions of experts; 3) testimony of witnesses.